Ally to adversary: mesenchymal stem cells and their transformation in leukaemia - Sharma, Mugdha (Cancer Cell Int, 2019)
Mesenchymal stem cells (MSC) are the key regulators of hematopoiesis. Owing to their dynamic nature; MSC differentiate into various lineages that further constitute the niche which are required for maintenance of the hematopoietic stem cells (HSC). A plethora of growth factors and cytokines secreted by MSC are essential for regulating the homeostasis within the niche in terms of cycling and quiescence of HSC. Additionally, there is a strong evidence suggesting the role of MSC in transformation of the niche to favour survival of leukemic cells. Regulation of HSC by MSC via BMP, Wnt, Notch and Sonic Hedgehog signalling has been well elaborated, however the modulation of MSC by HSC/LSC is yet unresolved. The cross talk between the HSC and MSC via paracrine or autocrine mechanisms is essential for the transformation. There are some reports implicating cell adhesion molecules, growth factors and cytokines; in modulation of MSC function and differentiation. The role of exosome mediated modulation has also been reported in the context of MSC transformation however, much needs to be done to understand this phenomenon in the present context. Similarly, the role of circulating nucleic acids, a well-studied molecular phenomenon in other tumours, requires attention in their potential role in crosstalk between MSC and HSC. This review underlines the current understanding of the physiological and pathophysiological roles of MSC and its transformation in diseased state, laying stress on developing further understanding of MSC regulation for development of the latter as therapeutic targets.